Day-case re-do varicose vein surgery. (July 2014) - Nagpal, Kamal; Glore, RJ; Chong, Peter Lee; Singh, Sewa; Pillay, Woolagasen; Tan, Peter; Cuschieri, RJ
Objective: To assess whether re-do varicose vein surgery as a day case is feasible and safe. Methods: Data were collected retrospectively on 70 consecutive patients (77 legs) undergoing re-do sapheno-femoral or sapheno-popliteal ligation by consultant surgeons as day cases. Follow-up was by structured telephone interview. Results: The 70 patients comprised 53 females and 17 males. Median age and body mass index were 47.5 years and 27, respectively. All patients were ASA Grade I or II. Median operating time was 75 min (range 25–140). Of the 70 patients intended to be treated as day cases, four (5.7%) were admitted overnight. There were no were re-admissions nor did any patient develop deep vein thrombosis. Eleven per cent developed wound infection and 4% transient lymphatic leakage. Overall, 91% of patients were pleased with the initial surgical result but this decreased to 81% in the longer term. Eighty-nine per cent would have their surgery performed again as a day case. Conclusion: Re-do sapheno-femoral or sapheno-popliteal can be performed safely as a day case.